Species of Aspergillus section Aspergillus from clinical samples in the United States. (9th October 2017) - Siqueira, João P Z; Sutton, Deanna A; Gené, Josepa; García, Dania; Wiederhold, Nathan; Guarro, Josep
Abstract: The diversity of Aspergillus species in clinical samples is continuously increasing. Species under the former name Eurotium, currently accommodated in section Aspergillus of the genus Aspergillus, are xerophilic fungi widely found in the human environment and able to grow on substrates with low water activity. However, their prevalence in the clinical setting is poorly known. We have studied the presence of these species in a set of clinical samples from the United States using a multilocus sequence analysis based on the internal transcribed spacer (ITS) region of the rRNA, and fragments of the genes β-tubulin ( BenA ), calmodulin ( CaM ), and polymerase II second largest subunit ( RPB2 ). A total of 25 isolates were studied and identified as follows: A. montevidensis (44%), A. chevalieri (36%), A. pseudoglaucus (8%), and A. costiformis (4%). A new species Aspergillus microperforatus is also proposed, which represented 8% of the isolates studied and is characterized by uniseriate conidial heads, subglobose to pyriform vesicles, rough conidia, globose to subglobose cleistothecia, and lenticular and smooth ascospores. The in vitro antifungal activity of eight clinically available antifungals was also determined against these isolates, with the echinocandins and posaconazole having the most potent activity.